Proof testing in support of the new San Francisco-Oakland Bay Bridge. - Seible, Frieder
Following the Loma Pieta earthquake, Caltrans (California Department of Transportation) started a multi-year seismic vulnerability assessment and retrofit project of all major bridges in California, including the San Francisco-Oakland Bay Bridge (SFOBB) East Bay Span. First, a retrofit of the East Span Steel Truss structure was evaluated. However, owing to the high cost and the questionable reliability in terms of performance of the retrofit and owing to its difficult implementation under full traffic, a replacement structure was determined to provide a seismically more reliable alternative, resulting in the SFOBB East Span Replacement Project. The new bridge consists of four distinct structures : (1) the Oakland landing or touchdown structures; (2) a segmental concrete box girder crossing called the Skyway; (3) a self anchored suspension (SAS) signature span; and (4) a series of multi-cell post-tensioned concrete box girder bridges providing the transition to the tunnel on Yerba Buena Island. The new bridge will feature parallel roadways and will be built next to the existing bridge, which will be dismantled after the new bridge is opened to traffic. This paper focuses only on the seismic safety aspects in the RC elements of three of the four segments of the new SFOBB East Span Bridge, namely the Skyway, the SAS bridge and the Oakland touchdown. Analytical and numerical models were developed to assess the seismic behavior of the Bay Bridge and a large scale proof testing program was conducted at the Charles Lee Powell Structural Research Laboratories at the University of California, San Diego. In the framework of this program, two steel shear links at 100 percent scale were tested, two concrete piers of the Skyway at 25 percent scale, a 25 percent scale model of the West Anchor Pier W2, and two column 35 percent scale piers of the Oakland Touchdown were also tested. The large scale tests on all structural elements of the new East Span of the San Francisco-Oakland Bay Bridge with expected inelastic performance characteristics proved that the design fully meets all performance requirements. The large or full scale tests were able to identify performance issues, resulting in design improvements and considerable cost savings. Alternative detailing and construction procedures were validated, leading to a more economic construction of the new bridge.
Keywords: San Francisco-Oakland Bay Bridge; Proof testing; Design; Steel shear links; Concrete piers